ATF4 promotes renal tubulointerstitial fibrosis through hexokinase II-mediated glycolysis - Feng, Songtao; Gao, Yueming; Wang, Zheng; Ni, Weijie; Zhou, Yan; Yuan, Mingyue; Ge, Jinyang; Sun, Lu; Liu, Bicheng; Qian, Hui; Li, Zuolin (Frontiers in Immunology, 2025)
BackgroundRenal tubulointerstitial fibrosis is a reliable predictor of progressive chronic kidney disease (CKD). Activating transcription factor 4 (ATF4) has recently emerged as a pivotal player in multiple pathophysiologic processes, particularly the stress response processes. This study aims to explore the role of ATF4 in tubulointerstitial fibrosis from a metabolic perspective.MethodsA murine model of renal fibrosis was generated via unilateral ureteral obstruction (UUO). Quantitative PCR was employed to assess the expression of inflammation-related genes and fibrotic markers in renal tissue, while Western blotting was used to quantify the corresponding protein levels. Immunohistochemistry was performed to determine the localization and expression patterns of ATF4. Lentivirus-mediated ATF4 knockdown mice, along with mice subjected to glycolytic inhibition, were subsequently employed to further investigate their effects on inflammatory mediators and fibrotic markers. In parallel, human renal proximal tubule epithelial cells (HK-2) were exposed to transforming growth factor-β1 (TGF-β1) to induce fibrosis in vitro. Subsequent molecular assays were performed to confirm the regulatory relationship between ATF4 and hexokinase II (HK-II), including verification of ATF4 binding to the HK2 promoter.ResultsWestern blotting and PCR analyses revealed a pronounced elevation of inflammatory cytokines, fibrotic markers, and ATF4 in the renal tissues of UUO mice compared with sham controls. Both in vitro and in vivo, ATF4 knockdown markedly mitigated tubular epithelial injury and fibrosis. Moreover, HK-II mRNA levels were significantly elevated in UUO renal tissues and in HK-2 cells stimulated with TGF-β1. Glycolytic inhibition effectively ameliorated tubular epithelial injury and fibrosis.ConclusionIn this study, we identified a marked induction of tubular ATF4 in mice subjected to UUO. Silencing ATF4 significantly mitigated renal tubulointerstitial fibrosis. Mechanistically, ATF4 was shown to act as a key glycolytic driver by transcriptionally upregulating hexokinase II. Collectively, these findings indicate that tubular ATF4 facilitates renal tubulointerstitial fibrosis through HK-II mediated glycolytic activation.